An analysis of slang words in Deadpool & Wolverine film (2024) - Yemic, Jim Marchel; Rahayu, Famala Eka Sanhadi (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2025)
This study examines the use of slang in the film Deadpool & Wolverine (2024), focusing on its forms and contextual meanings. Slang is a distinct feature of informal communication that reflects identity, creativity, and cultural belonging. The research applies a descriptive qualitative method, with data collected from the dialogues of the main characters in the film. The slang expressions are classified based on Allan and Burridge’s framework, which includes clipping, imitative, flippant, fresh and creative, and acronym types. The analysis shows that the film makes extensive use of slang, not only as a stylistic device but also as a means of character development and humor. The findings reveal that fresh and creative slang is the most frequently used, highlighting Deadpool’s humorous and playful personality, while other types such as flippant and imitative contribute to the depiction of sarcasm, casualness, and social bonding. Through these uses, slang becomes an essential part of the film’s dialogue, enriching its entertainment value and reflecting cultural expressions in contemporary media. This study concludes that the analysis of slang in film can provide deeper insight into language variation, identity, and cultural context.